Effect of water vapor content during the solid state synthesis of manganese-doped magnesium fluoro-germanate phosphor on its chemistry and photoluminescent properties - Ali, Amjad; Chepyga, Liudmyla; Khanzada, Laraib Sarfraz; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw (Optical Materials, 2020)
Several samples of magnesium fluoro-germanate doped with Mn4+ were prepared by solid state synthesis with a different water vapor content in the synthesis atmosphere. A significant decrease in quantum yield and emission intensity was observed with the increase in water vapor content during synthesis. Although there was little effect on the emission spectra, the changes in excitation spectra indicate the dominance of magnesium germanate instead of magnesium fluoro-germanate at high water vapor content. X-ray diffraction (XRD) results show that the pure phase was only achieved with the least amount of water vapor. Refinement of XRD data estimates the quantities of different phases present. The effect on the grain size and morphology is also remarkable, as demonstrated by scanning electron microscopy imaging. The reason behind the changes is discussed in detail. The temperature dependence of the photoluminescence spectra was measured between room temperature and 500 °C where the luminescence is quenched to nearly 3% of its initial value.
CRIS-Team Scopus Importer:2019-12-17
Keywords: Effect of humidity; Magnesium fluoro-germanate; Photoluminescence; Solid state reaction; Thermographic phosphor; Water vapor

Novel two-dimensional phosphor thermography by decay-time method using a low frame-rate CMOS camera - Ali, Amjad; Chepyga, Liudmyla; Khanzada, Laraib Sarfraz; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw (Optics and Lasers in Engineering, 2020)

Optimization of synthesis and compositional parameters of magnesium germanate and fluoro-germanate thermographic phosphors - Ali, Amjad; Khanzada, Laraib Sarfraz; Hashemi, Amir; Polzer, Carsten; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw (Journal of Alloys and Compounds, 2018)
Various documented formulations of magnesium germanate and flouro-germanate were synthesized by conventional solid state method at various temperatures to find out optimal synthesis conditions for maximum luminescence intensity. Relative efficiency of luminescence intensity and thermal stability of luminescence of these formulations is then discussed with respect to the commercially available phosphor. Mg28Ge7.5O38F10:Mn4+ was found to be the most efficient when synthesized at 1150 °C in air and has a comparable efficiency with respect to commercial sample. Photoluminescence intensity with increasing temperature was measured till 500 °C; the samples showed persistent emission till 300 °C. Relatively, samples with MgF2 give stronger emission at high temperatures if added in proper ratio.
Keywords: Mn4+ Red luminescence Magnesium fluoro-germanate Magnesium germanat Temperature dependent photoluminescence

Surface thermography using dual channel imaging based on the blue and red emission of Ba3MgSi2O8:Eu2+, Mn2+ - Hashemi, Amir; Gast, Jessica; Ali, Amjad; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph (Measurement Science and Technology, 2017)
In this investigation, we present a surface temperature determination method, based on the luminescence characteristics of Ba3MgSi2O8:Eu+2,Mn+2. Simple optics utilizing only one RGB scientific CMOS camera makes this measurement technique easily applicable. Four different imaging methods were developed and are presented together with the corresponding calibration curves. We successfully utilized the methods to take surface temperature gradient images of glass plates with a point heat source between them.
Keywords: Phosphor spectroscopy; Dual channel lock in method; Phase sensitive averaging detection method; Imaging; Temperature measurement; Photoluminescence decay; Intensity ratio

Synthesis and photoluminescent properties of the Dy3+ doped YSO as a high-temperature thermographic phosphor - Chepyga, Liudmyla; Hertle, Ellen Elisabeth; Ali, Amjad; Zigan, Lars; Osvet, Andres; Brabec, Christoph; Batentschuk, Miroslaw (Journal of Luminescence, 2018)
Dy3+-doped yttrium orthosilicate (Y2SiO5, abbreviated YSO) phosphors were synthesized: (1) by conventional high temperature solid-state method using two types of fluxes: lithium fluoride (LiF) and boron oxide (B2O3); (2) by metal alkoxide sol-gel method using isopropoxide assisted co-precipitation with subsequent annealing to explore its possible application in high-temperature thermometry. It was experimentally observed that the use of LiF flux affects the luminescent properties due to improvement of the crystal quality of crystallites and co-doping Li+ and F- ions. Herein, a strategy involving the use of different fluxes and concentration of Dy3+ ions has been developed to achieve high photoluminescence (PL) intensity and high intensity ratio of different PL peaks. The case of incorporated LiF in the host crystal lattices revealed strong enhancement of luminescence intensity of YSO:Dy (more than three times higher at 293 K) compared to the luminescence intensity of the phosphors synthesized with B2O3. Based on the results of high temperature measurements, it can be stated that YSO:Dy is a favorable phosphor for high temperature measurement, with a temperature sensitivity range comparable to YAG:Dy but with a lower PL decay time which is reduced by about 60%. For temperatures up to 1250 K the intensity ratio approach offers better measurement capabilities while the temperature sensitivity above 1250 K is superior for the decay time approach.
Keywords: Dysprosium; Luminescence; Phosphor thermometry; YSO